1989
DOI: 10.3171/jns.1989.71.2.0211
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lymphocyte function by glioblastoma-derived transforming growth factor β2

Abstract: Human glioblastoma cells secrete an inhibitory factor termed "glioblastoma-derived T-cell suppressor factor" (G-TsF). A member of the transforming growth factor beta (TGF beta) family, G-TsF is identical to TGF beta 2. The present study investigated the effect of G-TsF/TGF beta 2 on the proliferative and cytotoxic properties of tumor-infiltrating lymphocytes (TIL's) isolated from malignant gliomas after expansion in vitro with interleukin-2 (IL-2). The results demonstrate that the IL-2 (5 to 20 U/ml)-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(52 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…Glioma-mediated immunosuppression and downregulation of the host immune response has been associated with the release of immunosuppressive factors by glioma cells, for example, transforming growth factor (TGF)-b1, b2, and b3. [32][33][34][35][36][37][38] In addition to TGF-b, other factors capable of inhibiting immune function 37 include the cytokines interleukin (IL)-6 and IL-10, [39][40][41][42][43][44][45] prostaglandin E, [46][47][48][49][50] and gangliosides. 51 TGF-b1 and IL-10 act by suppressing T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma-mediated immunosuppression and downregulation of the host immune response has been associated with the release of immunosuppressive factors by glioma cells, for example, transforming growth factor (TGF)-b1, b2, and b3. [32][33][34][35][36][37][38] In addition to TGF-b, other factors capable of inhibiting immune function 37 include the cytokines interleukin (IL)-6 and IL-10, [39][40][41][42][43][44][45] prostaglandin E, [46][47][48][49][50] and gangliosides. 51 TGF-b1 and IL-10 act by suppressing T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, gliomas release factors such as transforming growth factor-beta (TGF-␤), which inhibit a number of functions of cytolytic T cells and NK cells. 10,11 Gliomas also express Fas ligand (CD95L), which induces apoptosis in immune effector cells. 12 A more recent study has demonstrated that human glioma cells produce substances that also suppress the function of antigen presenting cells (APCs).…”
Section: Expressing Tumors Tumor Angiogenesis Was Suppressed In Cytomentioning
confidence: 99%
“…GBM patients are profoundly immunosuppressive, both locally within the tumor and systemically (12). Multiple mechanisms exist to suppress effective immune responses targeted toward the tumor, including the blood-brain barrier that restricts lymphocyte trafficking (13), the local production of immunosuppressive cytokine transforming growth factor β (14,15), the increased expression of B7-H1 in glioma and the induction of T-cell apoptosis (16,17), the increased frequency of circulating regulatory T cells (18) and defective T-cell priming by microglial cells (19). On the other hand, stronger immune responses are associated with lower glioma incidences and/or increased survival.…”
Section: Introductionmentioning
confidence: 99%